An Examination of the Structural Validity of Instruments Assessing PE Teachers' Beliefs, Intentions, and Self-Efficacy towards Teaching Physically Active Classes - Trent D. Brown (MDPI AG, 2023)
Schools and, in particular, health and physical education (HPE) classes, has the potential to engage children and adolescents in health-enhancing physical activity. HPE teachers may enable or constrain this behaviour through appropriate classroom strategies and pedagogies that enhance not only student learning but also their engagement in physical activity. Such practices are a result of a teacher's curricula beliefs, self-efficacy, and intention to teach physical activity as part of their HPE classes. The purpose of this study is to investigate the structural validity of six instruments designed to assess teachers' beliefs, self-efficacy, and intentions regarding physical activity in physical education using the Rasch Measurement Model (RMM). Data suggest that three out of six instruments demonstrated multidimensional characteristics (curriculum beliefs, self-efficacy, and subjective norm). Model fit data were in the ranges of 0.5 to 1.61 for infit and −2.58 to 3.20 for outfit data. Differential item functioning was only present on one item in the curriculum beliefs instrument. Person reliability was >0.55 and item reliability was >0.73. Qualitative interpretation of Wright maps demonstrated a very good spread of items. Overall, each instrument demonstrated appropriate structural validity when weighed up against all of the components of the RMM.